2015
DOI: 10.1038/sc.2015.170
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study for risk factors for febrile UTI in spinal cord injury patients with routine concomitant intermittent catheterization in outpatient settings

Abstract: Study design: Retrospective study. Objectives: The objective of this study was to investigate the clinical risk factors for febrile urinary tract infection (UTI) in spinal cord injury-associated neurogenic bladder (NB) patients who perform routine clean intermittent catheterization (CIC). Setting: Rehabilitation Hospital, Kobe, Japan. Methods: Over a 3-year period, we retrospectively assessed the clinical risk factors for febrile UTI in 259 spinal cord injury patients diagnosed as NB and performing routine CIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…In a retrospective study on the risk factors associated with urinary tract infection (UTI) based on a Clinical Practice Guideline , intermittent catheterization was strongly recommended as the first choice in patients with a need for catheterization; however for those patients who needed more than three intermittent catheterizations/day or patients with paraplegia who are at high risk of urinary tract dysfunction, the urethral catheterization became vital 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study on the risk factors associated with urinary tract infection (UTI) based on a Clinical Practice Guideline , intermittent catheterization was strongly recommended as the first choice in patients with a need for catheterization; however for those patients who needed more than three intermittent catheterizations/day or patients with paraplegia who are at high risk of urinary tract dysfunction, the urethral catheterization became vital 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Esos hechos nos indican que el tratamiento para los pacientes con vejiga neurogénica, debe ser orientado de forma especial. [4][5][6][7] Patogénesis y Factores de Riesgo Patogénesis Se identificaron deficiencias en factores inmunes como el CD14 M y D88 cuando existe lesión medular, lo cual implica una alteración primaria en el sistema de reconocimiento de patógenos a la hora de controlar la infección. También en la respuesta pro y antiinflamatoria de la infección aguda.…”
Section: Epidemiologíaunclassified
“…4 Regarding UTI in NLUTD patients caused by spinal cord injury or dysfunction, symptomatic UTI reportedly occurs in 22%-45%. 5 Those patients often present without classic symptoms of UTIs but with abdominal or back pain, increased spasticity, and urinary incontinence. 6 Risk factors for UTIs among NLUTD patients are indwelling catheters, urinary stasis, high bladder pressure, and bladder stones.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that the annual rate of symptomatic UTI was 26% for quadriplegic patients doing CIC 4 . Regarding UTI in NLUTD patients caused by spinal cord injury or dysfunction, symptomatic UTI reportedly occurs in 22%–45% 5 . Those patients often present without classic symptoms of UTIs but with abdominal or back pain, increased spasticity, and urinary incontinence 6 …”
Section: Introductionmentioning
confidence: 99%